Identification of Bovine, Pig and Duck Meat Species in Mixtures and in Meat Products on the Basis of the mtDNA Cytochrome Oxidase Subunit I (COI) Gene Sequence - Spychaj Anita; Szalata Marlena; Słomski Ryszard; Pospiech Edward (Polish Journal of Food and Nutrition Sciences, 2016)
The aim of this study was to develop a method using PCR and self-designed primers on the basis of the mtDNA cytochrome oxidase subunit I (COI) gene sequence to enable direct identification of the meat of three species of animals, i.e. bovines, pigs and ducks, in the single type sample, in meat mixtures and meat products. The mixtures comprised up to six meat species including apart from beef, pork and duck also chicken, turkey and goose meat. The obtained results indicate the possibility of qualitative identification of the aforementioned meat species in all types of investigated food products. The maximum length of PCR products did not exceed 300 bp, which was supposed to favour the amplification of DNA from meat products which are usually thermally processed and/or exposed to high pressure. PCR primers hybridised selectively with bovine, pig and duck DNA, showing total species specificity.